Current analytical methods for amlodipine and its formulations: A review - Helal Uddin, A.B.M.; Alaama, Mohammed; Sarker, Md. Zaidul Islam; Abbas, S. A; Awang, Mohamed; Karim, Fahim Tamzeedul (Razi Publishing, 2017)
The use of amlodipine is very common due to the effects of amlodipine on hypertension and coronary artery disease (CAD) like chronic stable angina, vasospastic angina (Prinzmetal’s or variant angina), and angiographically documented CAD. Amlodipine is involved in several combinations with other antihypertensive drugs. The analysis of amlodipine and its co-drugs is reported using several analytical methods such as spectrophotometric, capillary electrophoresis and chromatographic methods. To our knowledge, there is no comprehensive reports which address all analytical methods for the analysis of amlodipine and combination, therefore we tried to gather as much as reports in one review paper to help researchers and industrial experts to easily access the information related to amlodipine analysis.